Reduction Behavior of Olanzapine and Its Differential Pulse Voltammetric Determination in Human Urine and Pharmaceuticals - Sultan Yağmur (Journal of Advanced Research in Natural and Applied Sciences)
The electrochemical reduction behavior of olanzapine was investigated by DPV (differential pulse voltammetry) and CV (cyclic voltammetry) techniques using a glassy carbon electrode. The measurements were carried out in different buffer solutions in a pH range from 0.50 to 12.05. The behavior of the peak potential and the peak current were examined by changing the pH, and a pH= 7.0 Britton-Robinson buffer solution was selected as the supporting electrolyte. To designate the electron and proton numbers that participated in the reaction, the changing peak potentials of olanzapine with increasing pH were investigated. The number of transferred electrons was found equal to the number of the hydrogen ions taking part in the electrode reaction. Equal electron and proton numbers were also supported with suggested reduction mechanism. For DPV analysis, the linear calibration curve of olanza-pine was plotted between concentrations 2x10-5M and 1x10-4M at the pH= 7.0 Britton-Robinson buffer solution. The limit of detection (LOD) and the limit of quantification (LOQ) were found to be 1.88x10-6 M and 6.29x10-6M, respectively. Lastly, the developed technique was applied to spiked urine and pharmaceutical preparations for recovery studies of olanzapine. A reaction mechanism related to the reduction of olanzapine was also proposed with this study.